A comparison of swallowing dysfunction in Becker muscular dystrophy and Duchenne muscular dystrophy. Issue 12 (5th June 2018) - Yamada, Yuka; Kawakami, Michiyuki; Wada, Ayako; Otsuka, Tomoyoshi; Muraoka, Kaori; Liu, Meigen
Abstract: Purpose: Swallowing dysfunction has been reported in Duchenne muscular dystrophy (DMD), but has not been studied in Becker muscular dystrophy (BMD). The aims of this study were to report the characteristics of swallowing dysfunction in BMD compared with DMD. Materials and methods: The study participants were 18 patients with BMD and 18 patients with DMD. All the patients were examined using videofluorography during swallowing of 5 mL of fluid. The penetration–aspiration scale (P–A scale) and the videofluorographic dysphagia scale (VDS) were used to evaluate dysphagia. Results: Swinyard functional ability stage was not significantly different between the BMD and DMD groups. Rate of aspiration, P–A scale score, and total VDS score did not differ across groups, but the VDS item score for laryngeal elevation was lower in the BMD group than in the DMD group (median scores 4.5 and 9, respectively; p < 0.001). In the BMD group, total VDS score significantly correlated with Swinyard stage ( r = 0.78, p < 0.001), but not with age or lung function. Conclusion: Patients with BMD have swallowing problems similar to those observed in patients with DMD when matched according to physical functional status. These patients should be evaluated and followed-up for the duration of their disease. Implications for rehabiliation: Dysphagia is one of the most critical problems in patients with progressive neuromuscular disease but dysphagia in patients with Becker muscular dystrophy (BMD) was not well known. Eighteen patients with BMD and 18 patients with Duchenne muscular dystrophy were examined with videofluorography. Patients with BMD have swallowing problems similar to those observed in patients with DMD.